Role of Popular Music Lyrics in Shaping Youth Identity: A Critical Discourse Analysis - Ramadhana, Florin; Heriyati, Nungki (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Popular music lyrics are not merely a form of entertainment but also function as potent cultural texts that shape and reflect youth identity. This study explores how contemporary popular songs construct and convey representations of adolescent identity through language. This study highlights the role of music as a site of identity negotiation, where adolescents interpret and internalize messages that influence their behaviors and values. By combining textual, discursive, and social dimensions of analysis. Using a qualitative-descriptive method and Critical Discourse Analysis (CDA) as the primary framework, the research investigates lyrics from selected international and Indonesian artists, including Billie Eilish, Taylor Swift, BTS, Raim Laode, and musicians from urban London. The analysis focuses on linguistic features, ideological structures, and social implications embedded in the lyrics. Discourse strategies such as metaphor, repetition, symbolism, and localized language are used to articulate personal and collective experiences.Findings indicate that popular music lyrics contribute to shaping emotional, gendered, and cultural identities among youth. Common themes include loneliness, empowerment, romantic ideals, social anxiety, and cultural belonging. Moreover, the lyrics often reflect or challenge prevailing ideologies related to gender norms, consumerism, and social expectations. this research reveals how popular music becomes a dynamic space for ideological contestation and identity formation. The findings offer valuable insights for scholars in literature, media studies, and cultural studies, emphasizing the importance of music in understanding the lived realities of youth in a globalized world.